2016
DOI: 10.1139/cjm-2015-0814
|View full text |Cite
|
Sign up to set email alerts
|

Faecal bacterial composition in dairy cows shedding Mycobacterium avium subsp. paratuberculosis in faeces in comparison with nonshedding cows

Abstract: The aim of this study was to determine possible differences in the faecal microbiota of dairy cows infected with Mycobacterium avium subsp. paratuberculosis (Johne's disease) in comparison with noninfected cows from the same herds. Faecal samples from cows in 4 herds were tested for M. avium subsp. paratuberculosis by real-time PCR, and faecal bacterial populations were analysed by 454 pyrosequencing of the 16S rRNA gene. The most notable differences between shedding and nonshedding cows were an increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…The core microbes of the terminal rectum were Firmicutes, Bacteroidetes and Proteobacteria [125]. These findings were consistent with other studies looking at rectum content in dairy cows [126] and fecal microbes in beef and dairy cattle [127][128][129][130]. Additionally, Wang et al determined that there were unique microbes associated with NS that may be also be associated with propionate and butyrate production [125].…”
Section: Ruminant Microbiomes In Health and Diseasesupporting
confidence: 85%
“…The core microbes of the terminal rectum were Firmicutes, Bacteroidetes and Proteobacteria [125]. These findings were consistent with other studies looking at rectum content in dairy cows [126] and fecal microbes in beef and dairy cattle [127][128][129][130]. Additionally, Wang et al determined that there were unique microbes associated with NS that may be also be associated with propionate and butyrate production [125].…”
Section: Ruminant Microbiomes In Health and Diseasesupporting
confidence: 85%
“…Of note, the molar proportion of acetate negatively correlated with the relative abundance of Psychrobacter (ρ = −0.61, P < 0.05) and Subdoligranulum (ρ = −0.54, P < 0.05), while that of propionate negatively correlated with the relative abundance of Escherichia-Shigella (ρ = −0.57, P < 0.05) in the ileum mucosa. The relative abundance of Psychrobacter has been observed to be higher in cows with Johne's disease compared with healthy ones (Kaevska et al, 2016). On the other hand, species belonging to Subdoligranulum produce butyrate (Eeckhaut et al, 2011), the production of which requires acetate as a key intermediate (De Vuyst and Leroy, 2011), and therefore the negative correlation between its abundance and acetate proportion can be expected.…”
Section: Correlation Between Molar Proportion Of Scfa and The Relative Abundance Of Mucosa-associated Bacteria In Ileum And Colonmentioning
confidence: 99%
“…The group also noted an enrichment of lysine and histidine metabolic pathways and an underrepresentation of glutathione metabolism and leucine and isoleucine degradation pathways within the ileal mucosa-associated microbiome of the MAP-infected cattle. Another study reported greater proportions of the genus Psychrobacter and reductions in the proportions of the genera Oscillospira , Ruminococcus and Bifidobacterium in cows infected with MAP [ 121 ], while in yet another [ 122 ], an altered fecal microbiota in cattle infected with MAP was also noted. More specifically, it was found that MAP positive animals had a higher abundance of Arthrobacter (from Actinobacteria) and Proteobacteria, Alistipes, Paraprevotella and Bacteroides were reduced in abundance compared to MAP negative animals.…”
Section: Introductionmentioning
confidence: 99%